2018
DOI: 10.3382/ps/pey230
|View full text |Cite
|
Sign up to set email alerts
|

Infectious bronchitis virus gel vaccination: evaluation of Mass-like (B-48) and 793/B-like (1/96) vaccine kinetics after combined administration at 1 day of age

Abstract: Infectious bronchitis (IB) control has a strong impact on poultry farming, because of the necessary epidemiological knowledge for planning the best strategy, the optimal strain association, the priming and boosting interventions. Broiler farming is even more problematic given the short and intense productive cycle, which requires an early onset of protection against most of the infectious threats, possibly with limited respiratory post-vaccination reactions that would have a direct impact on the bird health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The advantage of this technique is the increased ingestion of cocci oocysts that are currently used in cocci vaccine with live IBV, as shown in Figure 8F. This application system is currently trialed for IBV application for immunization against IBV [147,148]. However, laboratory study and commercial field trials revealed it to be more effective than spray vaccination [144,149,150].…”
Section: Gel Vaccinationmentioning
confidence: 99%
“…The advantage of this technique is the increased ingestion of cocci oocysts that are currently used in cocci vaccine with live IBV, as shown in Figure 8F. This application system is currently trialed for IBV application for immunization against IBV [147,148]. However, laboratory study and commercial field trials revealed it to be more effective than spray vaccination [144,149,150].…”
Section: Gel Vaccinationmentioning
confidence: 99%
“…Alternatively, an accessory evaluation of vaccine kinetics [ 68 ] and coverage [ 124 , 125 ] can be carried out by molecular assays (i.e., qRT-PCR), which quantify the vaccine titres replicating in the bird respiratory tract along the productive cycle. Because of the common persistence of the vaccines and the expected competition between vaccine and field strains for cellular receptors [ 68 , 82 ], the vaccine yield could be considered as a proxy of vaccination quality and protection, in addition to classical immunity assessment.…”
Section: Relevant Factors For Ibv Controlmentioning
confidence: 99%
“…Nevertheless, it is still used, mainly for booster administration of less attenuated vaccines in the field [ 83 ]. Gel vaccination, initially studied for coccidiosis [ 132 , 133 ], has also been applied to IBV providing a chemically stable environment, without altering the vaccine kinetics [ 124 , 134 ]. A possible beneficial impact of gel vaccination on the chick body temperature with respect to the spray technique has also been hypothesized, although consistent experimental confirmation is still lacking.…”
Section: Relevant Factors For Ibv Controlmentioning
confidence: 99%
“…In the poultry sector, they have been used for a long time to supply live coccidiosis vaccines [ 22 ] and more recently probiotics and prebiotics [ 23 ]. Some studies have reported that IBV vaccination by gel allows for a proper immunization in experimental conditions [ 23 , 24 , 25 , 26 ]. Compared to spray vaccination, it may also have the additional advantage of a lesser impact on chicks’ body temperature [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that IBV vaccination by gel allows for a proper immunization in experimental conditions [ 23 , 24 , 25 , 26 ]. Compared to spray vaccination, it may also have the additional advantage of a lesser impact on chicks’ body temperature [ 26 ].…”
Section: Introductionmentioning
confidence: 99%